SPIRITUAL TRANSFORMATION: A RELIGIOUS PERSPECTIVE FOR ADDRESSING GANGSTERISM THROUGH THE PRACTICES OF PADEPOKAN SAPU JAGAT EAST JAVA - Fadillah, Annisa; Arief, Dwi; Trianti, Rani; Pradana, Dhiyaa Rifqi; Azis, Abdul (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
The prevention and management of social issues that are considered normal are addressed using legal methods, such as implementing social penalties and legal-formal penalties through the court system. This study aims to propose a religious perspective as a means of addressing gangsterism. The research aims to elucidate the application of spiritual principles by the social institution, Padepokan Sapu Jagat, to those who have previously engaged in thuggery. This study employs a qualitative approach through the use of a case study methodology. Data gathering strategies were carried out in three ways, namely: 1) Firstly. The methods employed include the utilization of visual media such as photographs and movies, as well as direct observation at Padepokan Sapu Jagat Sukabumi. Conducted semi-structured interviews with 5 administrators of hermitages and 9 individuals who were previously involved in acts of thuggery. The findings indicated that Padepokan Sapu Jagad used the practice of pencak silat, which encompasses spiritual principles, as a method of exerting social influence over former delinquents. The spiritual ideals are derived from the Qur'an and Hadith, aiming to facilitate a constant transformation in the social conduct of former criminals.Pencegahan dan penanganan masalah sosial normatif dilakukan melalui pendekatan hukum, seperti pemberian sanksi sosial dan sanksi legal-formal melalui proses lembaga peradilan. Penelitian ini bermaksud menawarkan pendekatan relijius sebagai salah satu upaya untuk menangani premanisme. Fokus dari studi adalah mendeskripsikan bagaimana institusi sosial yakni Padepokan Sapu Jagat menerapkan nilai-nilai spiritual kepada mantan pelaku premanisme. Penelitian ini menggunakan metode kualitatif studi kasus. Teknik pengumpulan data dilakukan dengan tiga cara, yaitu: 1). Dokumentasi dalam bentuk foto dan video; 2) observasi ke Padepokan Sapu Jagat Sukabumi; dan 3). Wawancara semi terstruktur ke 5 pengurus padepokan dan 9 mantan pelaku aksi premanisme. Hasil penelitian menunjukan bahwa Padepokan Sapu Jagad menggunakan pencak silat yang memiliki muatan nilai-nilai spiritual sebagai sarana kontrol sosial para mantan preman. Nilai-nilai spiritual ini diambilkan dari teks Al Quran dan Hadist (perkataan Nabi Muhammad) dengan tujuan agar mantan preman dapat secara konsisten merubah perilaku sosial mereka.